Application of the Legal Clinic Method in Legal Education in Higher Education - Aryono, Aryo; Agung Saputro, M Susilo (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Social justice and human rights (HR) are fundamental elements in a fair legal system. However, the realization of these principles in Indonesia still faces various challenges, such as the increasing number of human rights violations, discrimination against minority groups, and limited access to education and legal services. The legal education system, which remains largely theoretical, also contributes to the gap between conceptual understanding and the practical skills of law students in addressing social justice and human rights issues. The clinical legal education (CLE) method serves as an innovative approach in legal education by providing students with direct experience in handling real cases. Through legal clinics, students develop legal analysis, negotiation, and advocacy skills, as well as a heightened social awareness. However, the implementation of this method in Indonesia still encounters obstacles, such as limited resources, regulatory barriers, and a lack of institutional support. This study aims to analyse the effectiveness of legal clinics in enhancing students' understanding and awareness of social justice and human rights. Using a qualitative approach, this research evaluates the design, implementation, and impact of student participation in clinical legal programs. The findings are expected to contribute to the development of a more practical and socially oriented legal education policy. With more systematic support from universities, the government, and legal institutions, legal clinics can serve as a strategic instrument in shaping a generation of legal professionals who are not only competent but also deeply committed to upholding human rights principles.